Study of The Lipid Hydrolisis Ability of Some Lipolytic Bacteria Species in Preserved Meat Combination Method of Lettuce Leaf Ensiling and Kepayang Seed Fermentation - Hidayati, Permata Ika (Proceeding INTERNATIONAL SEMINAR IMPROVING TROPICAL ANIMAL PRODUCTION FOR FOOD SECURITY)
Meat preservation with natural material use the combination method of lettuce leaf(Lactuca sativa) ensiling and kepayang seed (Pangium edule Reinw) fermentation is an easy, cheap,safely, and efficient preservation method that also could maintain the meat lipid contents. Thispreservation was done in order to prevent the meat from spoilage caused by bacteria. Preservedmeat at the end of storage time could be spoilage caused of contaminant bacteria that can decreasethe meat quality. This research was done to: (1) analyze the lipid hydrolysis ability of some lipolyticbacteria in preserved meat in a qualitative and quantitative manner; (2) analyze the decrease of thelipid content in preserved meat that were stored during 0, 7, 14, and 21 days. The lipid hydrolysisability of six bacteria species isolated from preserved meat were analyzed in qualitative manner byinoculate on Nutrient Agar added with meat oil and incubated in 370C during 1x24 hour. The lipidhydrolysis ability of lipolytic bacteria species were analyzed in quantitative manner by analyze thelipid content on preserved meat that were stored during 0, 7, 14, and 21 days use the nutrient brothmedium added with the meat oil. The research result shows that: (1) the six bacteria species isolatedfrom preserved meat were lipolytic bacteria; (2) Citrobacter freundii have the highest lipolytichydrolysis ability and Klebsiella rhinoscleromatis have the lowest lipolytic hydrolysis ability; (3) thelowest decrease of the lipid content is on the preserved meat that storage in 21 days.Key Words: Â Lettuce Leaf Ensiling Fermentation, Kepayang Seed Fermentation, Lipid Hydrolysis,Â Lipolytic Bacteria